A control approach for alternating current disturbance signal of fuel cells based on MOSFET high‐speed switch. Issue 3 (22nd May 2021) - Zhou, Y. F.; Dong, Q. C.; Huang, L. J.; Li, L. H.; Lian, J.
Abstract: Internal resistance is currently one of the most effective ways to achieve the performance improvement, control optimization, and on‐line fault diagnosis of fuel cells. In the fuel cell internal resistance test (FCIRT) system (FCIRTS), the alternating current (AC) disturbance signal is mainly achieved through the use of DC/DC converters or other expensive program‐controlled equipments, which are expensive and large, and it is not conducive to the commercial application of low‐cost FCIRTS. In particular, for the fuel cell vehicles based on dual‐source motors, the DC/DC structure is cancelled. Therefore, a new method should be used in the FCIRTS. To solve this problem, a low‐cost fuel cell AC disturbance signal control approach based on MOSFET high‐speed switch was proposed in this paper. In the approach, a circuit model of MOSFET high‐speed regulation was built, and the AC control of the fuel cells was achieved finally by simulation analysis and experimental verification. The proposed approach can not only independently control the AC components, but also save the system space and cost because of reducing reliance on DC/DC converters and dedicated equipments. Therefore, it is of great value to the development of low‐cost, high‐precision, and real‐time FCIRTS.